TECHNOLOGY READINESS LEVEL TEST OF INTEGRATED STEAM DISTILLATION AND DRYING SYSTEM (DRYSTILLA) BASED ON ELECTRONIC CONTROL - Dien Hawa, Sarah; Noor Prasetyono, Rizki; Syauqi, Achmad; Prayogi, Syaiful (Journal of Electronic and Electrical Power Applications, 2025)
Cardamom is a high-value spice commodity with significant potential as a raw material for essential oil production; however, its utilization at the village-farmer level remains dominated by the sale of raw materials due to limited postharvest technology. This study aims to experimentally evaluate the performance and Technology Readiness Level (TRL) of DryStilla, an integrated steam distillation and drying system specifically designed for small-scale, village-based cardamom processing. The research employs an engineering-based experimental method through field testing in a real operational environment at the Cardamom Berkarya Farmer Group in Karangkemiri Village. The evaluation focuses on technical performance, operational efficiency, essential oil yield, system stability, and initial economic impacts. The experimental results indicate that DryStilla reduces drying time from 2–3 days to 6–8 hours, increases essential oil yield by more than 50% (approximately 3.0–3.5%), and significantly reduces the loss of volatile compounds compared to conventional methods. The integrated drying and steam distillation system also improves energy efficiency, operational simplicity, and suitability for village-scale production. TRL assessment shows that DryStilla has achieved TRL levels 7–8, indicating that the system has been successfully demonstrated and operates stably in a real operational environment. These findings demonstrate that DryStilla has strong potential as an appropriate postharvest technology to support cardamom downstream processing, enhance product value, and strengthen the economic independence of rural farmers